2022
DOI: 10.3390/vaccines10122170
|View full text |Cite
|
Sign up to set email alerts
|

Ag85a-S2 Activates cGAS-STING Signaling Pathway in Intestinal Mucosal Cells

Abstract: Brucellosis is a zoonotic disease caused by Gram-negative bacteria. Most of the brucellosis vaccines in the application are whole-bacteria vaccines. Live-attenuated vaccines are widely used for brucellosis prevention in sheep, goats, pigs, and cattle. Thus, there is also a need for an adjuvanted vaccine for human brucellosis, because the attenuated Brucella vaccines now utilized in animals cause human illness. Here, we developed a live-attenuated Brucella suis strain 2 vaccine (S2) adjuvanted with Ag85a (Ag85a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the 2nd edition of the special issue, Dang et al developed a novel adjuvanted live-attenuated vaccine for human brucellosis, which is a zoonotic bacterial disease [ 21 ]. The existing live-attenuated Brucella vaccines cause reproductive health issues in cattle and were potentially pathogenic in humans due to the high dosage requirement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2nd edition of the special issue, Dang et al developed a novel adjuvanted live-attenuated vaccine for human brucellosis, which is a zoonotic bacterial disease [ 21 ]. The existing live-attenuated Brucella vaccines cause reproductive health issues in cattle and were potentially pathogenic in humans due to the high dosage requirement.…”
mentioning
confidence: 99%
“…In this study, the authors have demonstrated that the use of Ag85a (a Mycobacterium tuberculosis cell wall derived diacylglycerol acyltransferase involved in lipid body formation) as an immune modulatory adjuvant significantly enhances CD4 + T and CD8 + T lymphocyte responses compared to vaccine alone. Knockout studies suggested that Ag85a achieves this protective immune response by activating the cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) signaling pathway and, hence, could be a solution to circumvent the high dose associated toxicity of live-attenuated Brucella vaccines in animals and humans [ 21 ].…”
mentioning
confidence: 99%